Influencing Factors of Commercial Energy Consumption Intention of Rural Residents: Evidence from Rural Chengdu - Aichun Jiang; Qian Zhong; Yan Wang; Yibin Ao; Chuan Chen (Energies, 2021)
With rapid rural urbanization and new rural construction, the commercial energy consumption of rural residents shows a trend of rapid growth, and China’s rural areas are also faced with environmental challenges brought by the increase of commercial energy consumption. China’s commercial energy consumption behavior of rural residents has also undergone tremendous changes. However, scholars have neglected the research on rural residents’ commercial energy consumption intention from a micro perspective. Therefore, this study takes the 5 villages in Chengdu out of the 100 representative villages in the Sichuan province as examples. From the perspective of the head of a family of permanent rural residents, extended planned behavior theory, exploratory factor analysis, and structural equation modeling are used to explore the influencing factors of rural resident commercial energy consumption intention and their relationship. Findings show that subjective norm, perceived behavioral control (PBC), and habit significantly affect residents’ behavioral intention. Habits significantly influence subjective norms and PBC. Therefore, in the new rural construction, rural residents are the main body and participants of energy consumption. Local government departments should plan reasonably according to the needs and characteristics of residents, constantly improve commercial energy infrastructure, improve service level, and further strengthen farmers’ attitude and satisfaction toward commercial energy. Moreover, they should increase the publicity and education of commercial energy, advocate green housing, and promote energy saving consumption reduction, and sustainable development in new rural areas.